Short-time response of soil ecological stoichiometry on aboveground biomass under fertilizer application of mixed grass pasture in the Northern Tibetan Plateau - Zhou, Juanjuan; Xia, Fei; Cao, Wenxia; Wei, Wei (PloS one, 2025)
The construction of artificial grasslands using native species is an effective measure to restore degraded grassland. In this study, three native grass species, Elymus nutans , Elymus tangutorum and Poa albertii subsp. poophagorum, domesticated in the northern Tibetan Plateau were used as test subjects. Three monocultures of E. nutans, E. tangutorum and P. albertii subsp. poophagorum and four mixed combinations E. nutans +E. tangutorum , E. nutans +P. albertii subsp. poophagorum, E. tangutorum +P. albertii subsp. poophagorum and E. nutans + E. tangutorum + P. albertii subsp. poophagorum were set up, with 7 sowing types as the main zones, and nested fertilization and non-fertilization as the secondary zones. The optimal sowing combinations were selected to clarify the community growth dynamics of different grass pasture, and to investigate the transgressive overyielding and diversity effects of artificial grassland and the response of soil chemometrics to fertilizer application, with a view to providing a scientific basis for ecological restoration of degraded grassland in the northern Tibetan Plateau. The results show that the different sowing combinations of grassland all exhibit obvious dynamic population change in the growing season, with aboveground biomass peaking on 20 September. The type of E. nutans is the dominant community of the mixed combinations. The forage yield was highest in the combination, and the fertilization treatment significantly increased the forage yield. E. nutans + E. tangutorum + P. albertii subsp. poophagorum mixed sowing with fertilizer application is the recommended methodology to establish artificial grassland in the northern Tibetan Plateau. The relative yield totals of the mixed combinations were all greater than 1, and all were transgressive overyielding. Combined with the analysis of the distribution of soil ecological stoichiometric characteristics under fertilizer and non-fertilizer treatments, it was found that aboveground biomass and transgressive overyielding coefficients responded to soil ecological stoichiometry in completely different ways. Under the unfertilized treatment, soil C, N and P are regulated primarily through microbial stoichiometry under the resource dependence of soil dissolved nutrient stoichiometry, which affected aboveground of artificial grassland. Under the fertilizer treatment, microbially mediated extracellular enzyme stoichiometry was dynamically changing to regulate the new substrate environmental supply and demand balance derived from fertilizer application. Future studies should examine the long-term impacts of these combinations across diverse environments by integrating complementary restoration techniques to improve artificial grassland sustainability, thereby offering scientific support for regional ecological restoration efforts.